Category-terminological apparatus of modern social upbringing - Z. A. Aksyutina (Образование и наука)
Introduction. Social upbringing has taken shape in the branch of pedagogical knowledge – the pedagogy of social upbringing, and its categorical and terminological apparatus remains unformed and imperfect. This leads to the arbitrariness of the description of social and educational phenomena in the theory and practice of social upbringing; loss of categorisation, meaning of terms and their incompleteness that results in the inconsistency of social upbringing theory, etc.Aim. The aim of the present article is a theoretical substantiation and description of the category-terminological apparatus of modern social upbringing based on the developed category classification, which acts as a means of systematising scientific knowledge.Methodology and research methods. The methodological foundations of the study were categorical, systemic and holistic approaches. Theoretical methods were used as research methods: categorical analysis and synthesis, methods of classification, systematisation and generalisation, categorical methods of triadic decoding of categories and permutations.Results. The study describes a two-level classification of categories developed by the author. Categories of the first order are allocated on the basis of purpose, include in their composition: base category, system and process categories. Categories of the second order are allocated on the basis of the use of mechanisms for the formation of categories, contain in their composition: a key category, synthesised, integrated and additional categories. The categorical system of social education is described. The categorical system of social upbringing is understood as a specially developed form of organisation of scientific knowledge, which makes it possible to holistically represent the objects of social education through given meaningful relationships between categories in the totality of their interaction.Scientific novelty. The scientific novelty of the study is the formation of a categorical system of social upbringing through a category-terminological apparatus, which provides the terminological unity of theory and practice, supplementing and concretising them and ensuring consistency and integrity. The developed categorical system of social upbringing does not change, but complements the specific scientific level of pedagogy methodology. By ensuring the completeness of the categorical apparatus, thecomplex of methods used in the analysis of the categories of social upbringing, enriches the technological level of pedagogy methodology with new methods of triadic decoding of categories and permutations. A new level of development of professional speech is being formed on the basis of its scientifically substantiated filling with a categorical system of social upbringing.Practical significance. The practical significance of the study lies in the fact that the categorical system of social upbringing can be used in the development of basic educational programmes of the psychological and pedagogical direction, training courses, methodological materials, in terms of the formation of students’ professional competencies; in the implementation of scientific research in the field of social pedagogy and social upbringing; in the development of dictionary-encyclopedic literature on social pedagogy and social upbringing. The holistic development of the categorical system will contribute to the enrichment of the terminology of social upbringing and the effectiveness of professional communication.